Bailias de abril: lirismo e política na reescrita dos cantares de amigo de Natália Correia - Gomes, Anália Sofia Cordeiro de Lima (2019)
The present research aims to study the poetic production of militancy of Natalia Correia and it’s inserted in the fields of cultural, gender and medieval studies, specifically on the Bailia/bailadas songs inserted in the Unpublished post 1990, found in the work O Sol nas Noites e o Luar nos Dias II, published in 1999. The still scarce scholarly collection on Troubadourism, as well as the rare studies on Neotrovadorism written by women, especially on the dictatorial period, justify the intention of the work by intertwining the resonances of Galician-Portuguese troubadour literature in contemporary Portuguese poetry. Initially, the author's life and work, her subversive relation to the dictatorial period and her bias of the struggle for women's causes, will be discussed: The Mátria. Next, a historical survey will be done on the period of the Galician-Portuguese troubadours, the female presence in the medieval rural scene and the approaches of Natália Correia with the Medieval period. Finally, the analysis of her neotrovadorescan songs will be done with regard to the universe of bailias/bailadas. This study will be guided by the theories of Flores (2017), Furlan (2017), Bueno (1968) Spina (1956/1971), Lapa (1970), Correia (2003). There will also be the contributions of some of the most renowned researchers that approach Neotrovadorism as Maleval (2002), Lopez (1997).